2012
DOI: 10.1111/j.1365-3164.2012.01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Owner assessment of therapeutic interventions for canine atopic dermatitis: a long‐term retrospective analysis

Abstract: This study revealed that clients believe antihistamines can be a useful part of multimodal therapy for canine atopic dermatitis. The results also demonstrated that a significant number of canines benefited from dietary modification. In addition, allergen-specific immunotherapy was the only treatment to induce true clinical remission of atopic dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Withdrawal of oral glucocorticoid treatment was achieved after Allermmune â HDM therapy in six cases (46.2%), suggesting higher response rates compared to those of previous reports on ASIT (5.0-21.5%). [14][15][16][17][18] Allermmune â HDM contains the recombinant mite allergen (Der f 2) manufactured by expressing Der f 2, a major mite allergen protein of CAD, in silkworms. The purified Der f 2 is then conjugated with pullulan (forming Der f 2-P).…”
Section: Discussionmentioning
confidence: 99%
“…Withdrawal of oral glucocorticoid treatment was achieved after Allermmune â HDM therapy in six cases (46.2%), suggesting higher response rates compared to those of previous reports on ASIT (5.0-21.5%). [14][15][16][17][18] Allermmune â HDM contains the recombinant mite allergen (Der f 2) manufactured by expressing Der f 2, a major mite allergen protein of CAD, in silkworms. The purified Der f 2 is then conjugated with pullulan (forming Der f 2-P).…”
Section: Discussionmentioning
confidence: 99%
“…Many dogs on AIT in this study received concurrent antipruritic therapy. Multimodal therapy is commonly needed in canine atopic dermatitis (4,24,25). However, after rush AIT in most dogs those were restricted to medications with few and mild adverse effects.…”
Section: Tab 4 üBerblick Zur Medikationmentioning
confidence: 99%
“…There is no evidence supporting the use of topical type 1 antihistamine formulations to treat canine AD (SOR C). Basis for such recommendations: Approximately 25 % of clients that gave oral antihistamines to their atopic dogs reported these to be at least very effective in a retrospective survey (QOE 2) [ 15 ]. An RCT reported that two oral antihistamines, a hydroxyzine and chlorpheniramine combination (Histacalmine, Virbac) and dimetindene (Fenistil, Novartis), mildly improved pruritus and skin lesions in dogs with AD (QOE 2) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%